The Role Of The Asean Intergovernmental Commission Of Human Rights In Giving Protection To The Ethics Rohingya Of The Spirit In Southeast Asia - Endah Rantau Itasari (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
The purpose of this study is to provide legal protection to the ethnic Rohingya, with the ASEAN Charter and the establishment of the ASEAN Intergovernmental Commission of Human Rights will strengthen the instruments in protecting human rights in ASEAN. Philosophically with the establishment of the ASEAN Intergovernmental Commission of Human Rights, member countries would prefer a regional settlement to an international one. Regional settlements were chosen because the rules are adapted to regional conditions. This ASEAN Intergovernmental Commission of Human Rights needs a strong foundation and position to be able to give a reprimand. Rohingya is one example of ASEAN's failure to guarantee human rights in the region. If this conflict cannot be resolved, of course, it is possible that future human rights violations will occur again. This research is a normative juridical study, the ASEAN Intergovernmental Commission of Human Rights is obliged to provide protection to ethnic Rohingya because the violation occurred in the Southeast Asia region and it is time for ASEAN member countries to give strict sanctions to Myamar due to the behavior given to the Rohingya ethnicity. The principle of non-intervention contained in the ASEAN Way will always be a barrier for ASEAN member countries in providing protection to ethnic Rohingya in Myanmar, but ASEAN member countries must continue to persuade Myanmar to respect every human right without exception. and ask for help from the international community to pressure Myanmar to stop persecuting the Rohingya.